A panel based on three-miRNAs as diagnostic biomarker for prostate cancer - Chen, Siwei; Lu, Chong; Lin, Shengjie; Sun, Chen; Wen, Zhenyu; Ge, Zhenjian; Chen, Wenkang; Li, Yingqi; Zhang, Pengwu; Wu, Yutong; Wang, Wuping; Zhou, Huimei; et al. (Frontiers in Genetics, 2024)
Background: Background: Prostate cancer (PCa) is one of the most prevalent malignancies affecting the male life cycle. The incidence and mortality of prostate cancer are also increasing every year. Detection of MicroRNA expression in serum to diagnose prostate cancer and determine prognosis is a very promising non-invasive modality.A total of 224 study participants were included in our study, including 112 prostate cancer patients and 112 healthy adults. The experiment consisted of three main phases, namely the screening phase, the testing phase, and the validation phase. The expression levels of serum miRNAs in patients and healthy adults were detected using quantitative reverse transcription-polymerase chain reaction. Receiver operating characteristic (ROC) curves and the area under the curve (AUC) were used to evaluate the diagnostic ability, specificity, and sensitivity of the candidate miRNAs.Result: Eventually, three miRNAs most relevant to prostate cancer diagnosis were selected, namely miR-106b-5p, miR-129-1-3p and miR-381-3p. We used these three miRNAs to construct a diagnostic panel with very high diagnostic potential for prostate cancer, which had an AUC of 0.912 (95% CI: 0.858 to 0.950; P<0.001; sensitivity=91.67%; specificity=79.76%). In addition, the three target genes (DTNA, GJB1, and TRPC4) we searched for are also expected to be used for prostate cancer diagnosis and treatment in the future.